Additive basal area in Knysna Forest - myth or reality? - Parker, Ruth (Department of Biological Sciences, 2017)
This paper explores the additive basal area phenomenon wherein the basal area of large above-canopy trees in a plot appears additive or extra to the total basal area of the plot. The mean basal area of Podocarpus falcatus and Podocarpus latifolius in 0.04 ha plots were studied in 2032 plots at eleven sites in the Knysna Forest in relation to the basal area of the remaining species and the total basal area. Mean basal area regressions indicated that the basal area of P. falcatus and P. latifolius were 'additive'. The basal area of plots with big trees and those without were compared and significant differences provided further support for this 'additive basal area' theory.